POTENSI PEMANFAATAN LIMBAH CAIR TAHU MENJADI BIOGAS UNTUK SKALA INDUSTRI RUMAH TANGGA DI PROVINSI BANTEN - Sally Sally; Yessica Putri Budianto; Meutia Wafa’ K. Hakim; Warsono El Kiyat (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
Tofu is one of the most produced and consumed foods in Indonesia as a source of protein. At present, most of the tofu producers located in Indonesia are a home industry with simple equipment, especially in Banten. The production of tofu mostly produces solid and liquid wastes. However, the liquid waste contains high protein and amino acids that can pollute the environment if it is not treated properly. It is due to this waste has a high BOD, COD and TSS value. Therefore, the right method is needed in utilizing tofu liquid waste by tofu producers in Indonesia by biogas production. Biogas from liquid waste can be produced as methane or hydrogen. Tofu waste based biogas provided benefits from various aspects, such as environmental, economic, social and health aspects. On the other hand, tofu waste production can be one of the efforts to achieve the Sustainable Development Goals (SDGs) in Banten. It can be implemented to achieve clean water and sanitation points, as well as affordable and clean energy sources